Clinicoepidemiologic Profile of Pediatric Traumatic Brain Injury: Experience of a Tertiary Care Hospital From Northern India. (December 2020) - Madaan, Priyanka; Agrawal, Deepak; Gupta, Deepak; Kumar, Atin; Jauhari, Prashant; Chakrabarty, Biswaroop; Pandey, R. M.; Paul, Vinod Kumar; Misra, M. C.; Gulati, Sheffali
Traumatic brain injury is an important cause of acquired brain injury. The current study brings to light the clinicoepidemiologic profile of pediatric traumatic brain injury in India. Retrospective record analysis of children (aged ≤ 16 years) with traumatic brain injury presenting to an apex-trauma-center in North India over 4 years was done. Of more than 15 000 patients with a suspected head injury, 4833 were children ≤16 years old. Of these, 1074 were admitted to the inpatient department; 65% were boys with a mean age at presentation being 6.6 years. Most patients (85%) had a Glasgow Coma Scale score of 13 to 15 at presentation while Glasgow Coma Scale scores of ≤8 was seen in 10% of patients. Neuroimaging (computed tomography [CT]) abnormalities were seen in 12% of patients, with the commonest abnormality being skull fracture, followed by contusions, and extradural hemorrhage. Around 2% of patients required decompressive craniotomy whereas 3% of patients succumbed to their illness. Among the inpatients with pediatric traumatic brain injury, two-thirds were boys with a mean age at presentation of 7.6 years. Severity of traumatic brain injury varied as mild (64%), moderate (11%), and severe (25%). The most common mode of injury was accidental falls (59%) followed by road traffic and rail accidents (34%). Neuroimaging abnormalities were seen in half of inpatients with pediatric traumatic brain injury, with the commonest abnormality being skull fracture. Pediatric head injuries are an important public health problem and constitute a third of all head injuries. They are more common in boys, and the most common modes of injury are accidental falls, followed by road traffic accidents.